TEK SENG BIO TEMPLE AS A SYMBOL OF HISTORY AND LOCALITY OF THE CHINESE INDONESIAN COMMUNITY IN CIKARANG - Farinuddin, Harry; Pradjoko, Didik (International Review of Humanities Studies, 2024)
This article examines Tek Seng Bio (德圣庙) Temple within the context of the temple as the symbol of local history among Chinese Indonesians in Cikarang. Established in 1900 by Tjio Lo Weh (蒋維内) from Fujian, the temple marked the inception of a Chinese settlement in North Cikarang. Unique in its devotion to Lín Tài Shī Gōng/Liem Tay Soe Kong (林太师公) as their main deity, Tek Seng Bio Temple originally functioned as a private familial place of worship. However, its transition to a public worship house faced challenges in 1967, with Presidential Instruction Number 14 imposing restrictions on Chinese religious practices, citing negative psychological and moral impacts on Indonesian society. In response to the governmental order, Tek Seng Bio Temple transformed itself into Dipankara Monastery in 1984. This adaptation facilitated the convergence of Theravada and Tridarma Buddhist worship, accommodating adherents of Confucianism and Taoism. Dipankara Monastery serves as a focal point for Chinese Buddhists, emphasising ancestor worship and traditional celebrations. Concurrently, Sariputra Monastery, established in 1991 adjacent to Tek Seng Bio Temple and even briefly occupying the front yard of Tek Seng Bio Temple before Sariputra had their own building, focuses on spiritual worship and education for pure Theravada and Chinese Buddhists in North Cikarang. This pioneering research constitutes the first comprehensive exploration of Tek Seng Bio Temple’s locality. Utilising primary source interviews, archival documentation, photographs, and fieldwork research, the study aims to contribute to the local historiography of North Cikarang, enhancing historical insights into the Chinese, Buddhist, Confucian, and Taoist communities in Indonesia. By meticulously examining the temple’s evolution and adaptation to external constraints, this research seeks to enrich our understanding of the complex interplay between religious practices, governmental regulations, and the cultural identity of Chinese Indonesians in Cikarang.